Do Tax Aggressiveness And Dividend Policy Affect The Relationship Between Earnings Management And Cost Of Debt? Case In Energy Sector Indonesia - Kartika Sitorus; Abdurrahman Abdurrahman; Eka Bertuah; Sapto Jumono (Cita Konsultindo Research Center, 2023)
Our study investigates how earnings management affects the cost of debt in energy sector firms on the Indonesian Stock Exchange (IDX) period 2015 to 2021. It further involves mediating and moderating the effect of tax aggressiveness and dividend policy. The Structural Equation Modeling (SEM) approach was used to analyze 315 panel data. We found a negative effect of earnings management and audit quality on the cost of debt. Earnings management is found to have a positive effect on tax aggressiveness, while tax aggressiveness has a negative impact on the cost of debt. Tax aggressiveness mediates earnings management-cost of debt effect exhibiting a negative correlation. Lastly, dividend policy is able to strengthen the effect of earnings management on the cost of debt. This research is intended to provide managerial implications for the companies and creditors regarding the asymmetry of financial report information. Policy implications, particularly for fiscal regulators pertaining to tax aggressiveness and financial services authorities concerned with assessing the capability of prospective debtors.